Development of Software for the Design of Differential Pressure Flowmeters in Accordance with the Updated ISO 5167:2022 - Масняк, Олег; Вишневська, Соломія-Анна (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2025)
This paper presents a study on the relevance of developing new software that implements the updated ISO 5167:2022 standard. The market for automating the design of variable pressure differential flowmeters was studied, and it was determined that with the successful launch of the software as a web application, there could be approximately 5,000-7,000 users worldwide. The main competitors of the future application were studied, namely FLOWCALC32, САПР «ВИТРАТОМІР» and AFT FATHOM. Based on the functionality of analogues, a competitive matrix was constructed indicating the advantages of the new DifFlow product. У цій роботі авторами проведено дослідження актуальності розробки нового програмного забезпечення, що імплементує оновлений стандарт ISO 5167:2022. Досліджено ринок автоматизації проєктування витратомірів змінного перепаду тиску та визначено, що при успішному запуску програмного забезпечення у вигляді вебзастосунка може бути близько 5,000-7,000 користувачів у всьому світі. Вивчено головних конкурентів майбутнього застосунку, а саме FLOWCALC32, САПР “ВИТРАТОМІР” та AFT FATHOM. На основі функціоналу аналогів було побудовано конкурентну матрицю з вказанням переваг нового продукту DifFlow.